Analysis of Women’s Representation in Various Positions and Roles within the Public Sector - Permatasari, Mutiara Indah; Harirah, Zulfa (Jurnal Ilmu Administrasi Negara (JUAN), 2025)
The representation of women in high-ranking positions within Indonesia’s public sector remains significantly low, despite the increasing number of female civil servants (ASN) and their comparable levels of education to male counterparts. This situation reflects a persistent gender imbalance in bureaucratic leadership that contradicts the principles of equality outlined in Law No. 5 of 2014 concerning the State Civil Apparatus, which guarantees equal opportunity for all citizens. The purpose of this study is to analyze the level of women’s representation in various public sector positions and to identify the key factors contributing to the underrepresentation of women in strategic leadership roles. The research adopts a qualitative approach using the library research method, employing the theories of Representative Bureaucracy and Glass Walls as analytical frameworks. Data were collected through extensive review of scholarly literature, government regulations, and statistical reports from the National Civil Service Agency (BKN). The results show that over the past three years, male civil servants have dominated senior leadership positions Principal, Middle, and Primary levels comprising approximately 80%, while women account for less than 20%. The findings indicate that the limited representation of women is primarily caused by low interest and self-confidence, limited lobbying ability, gender-based job segregation, and enduring negative stereotypes that associate leadership with masculine traits. The study concludes that gender equality in Indonesia’s bureaucracy is still far from being realized, and achieving representative bureaucracy requires stronger institutional commitment to empowering women, promoting gender-sensitive recruitment, and ensuring equitable access to leadership opportunities in public administration.